Pernicious Behavior: the Effect of the Consequences in the Choice between to Harm/do not Harm a Classmate - Carpio Ramírez, Claudio Antonio (Pontificia Universidad Javeriana, 2018)
This research was based on two main interbehavioral suppositions: 1) Behavior is likely modulated by historical and/or situational factors; 2) Pernicious behavior can be regulated by situational factors such as the consequences. The objective was to evaluate the effect of the consequences (positives and negatives) on the choice between to harm or do not harm a classmate while solving a task. Thirty-five college students were randomly assigned into one of five experimental groups. The task consisted in solving arithmetic operations proportionally scored from 1 to 5 points. The results are discussed in terms of the regulatory role of the consequences (in relation to pernicious behavior) as a situational factor. The main result was that the negative consequences by the choice of do not harm the partner mainly modulated the occurrence of pernicious behavior.